Nordic walking - the healthiest sport ever? - A review - Angelika Szpulak; Aleksandra Makłowicz; Ewelina Kopczyńska; Agata Frańczuk; Michalina Grzelka; Julia Głoskowska; Katarzyna Kuleta; Katarzyna Słychan; Katarzyna Kuśmierczyk; Patrycja Karkos (Nicolaus Copernicus University in Toruń, 2024)
Nordic Walking (NW) is a widely practiced sport that was originally intended as a way for cross-country skiers to get a year-round workout. However, it quickly proved to be easy, enjoyable and undemanding, which led populations around the world to train NW. Today, the sport is used as rehabilitation in most medical specialties, as it is considered to be safe, not creating barriers, inexpensive and has no side effects. This article presents a literature review on the effects of NW on patients' mental and physical health.